2020
DOI: 10.1111/ctr.13831
|View full text |Cite
|
Sign up to set email alerts
|

Options for the treatment of intrahepatic recurrent hepatocellular carcinoma: Salvage liver transplantation or rehepatectomy?

Abstract: Objective: To explore prognostic factors by comparing the efficacy of salvage liver transplantation (sLT) and rehepatectomy (RH) for the treatment of recurrent hepatocellular carcinoma after hepatectomy. Methods:Clinical data were collected for 124 patients treated at our center from January 2012 to August 2018. The median follow-up time for the patients was 39 months. By analyzing the clinical data between the sLT group (46 cases) and RH group (78 cases), the factors affecting the prognosis of patients were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Most patients with RHCC cannot undergo liver resection or salvage liver transplantation to achieve a cure because they commonly have low liver function due to cirrhosis and there is a worldwide shortage of livers available for transplantation. [19][20][21] Currently, RFA and TACE are widely used in patients with unresectable recurrent liver lesions. RFA was first used for recurrent liver cancer in 1999, and therefore, patients with RHCC have more therapy options in addition to rehepatectomy.…”
Section: Discussionmentioning
confidence: 99%
“…Most patients with RHCC cannot undergo liver resection or salvage liver transplantation to achieve a cure because they commonly have low liver function due to cirrhosis and there is a worldwide shortage of livers available for transplantation. [19][20][21] Currently, RFA and TACE are widely used in patients with unresectable recurrent liver lesions. RFA was first used for recurrent liver cancer in 1999, and therefore, patients with RHCC have more therapy options in addition to rehepatectomy.…”
Section: Discussionmentioning
confidence: 99%
“…However, the advantage of SLT over RH was not confirmed when only patients with higher AFP at recurrence (>100 ng/mL) were considered, indicating that the selection process for RH versus SLT is complex. Furthermore, Fang et al [139] reported longer operation time, increased blood loss and blood replacement, prolonged in-hospital stays and postoperative morbidity in the case of SLT; in addition, perioperative mortality was not reported for the groups.…”
Section: Rh Vs Slt: Which Is the Best Option?mentioning
confidence: 97%
“…Several studies have reported a comparison between SLT and RH in the case of rHCC (Table 2) [119,[137][138][139][140]. Clearly, there are many factors to be considered, not least the experience of a given centre in performing both liver resection and transplantation.…”
Section: Rh Vs Slt: Which Is the Best Option?mentioning
confidence: 99%
See 1 more Smart Citation
“…SLT is considered an effective and curative treatment approach that can simultaneously resolve liver tumors, potential liver dysfunction and the original underlying diseases. For recurrent HCC, as long as patients meet the criteria, the prognosis is relatively high[ 11 , 82 , 83 ]; the 5-year survival rate is 42%-73%[ 84 ]. A systematic retrospective analysis of the prognosis of SLT and RR in the treatment of recurrent HCC showed that patients in the SLT group generally had larger liver lesions but better relapse-free survival (RFS) than those in the RR group and that the OS of the two groups was similar[ 85 ].…”
Section: Liver-targeted Local Therapy Still Dominatesmentioning
confidence: 99%